Managing surgical demand when needs outstrip resource: qualitative investigation of colorectal cancer surgery provision in the first wave of the COVID-19 pandemic. Issue 1 (7th November 2022) - Conefrey, Carmel; Ochieng, Cynthia; Hoffman, Christin; Elliott, Daisy; Avery, Kerry; Bennett, Joanne; Blencowe, Natalie; Duff, Sarah; Kinross, James; McNair, Angus; Messenger, David; Pullybank, Anne; et al.
Abstract: Background: At the onset of the COVID-19 pandemic, elective surgical provision was severely affected by the need for hospital reorganization to care for critically ill patients. In response, National Health Service (NHS) England issued national guidance proposing acceptable time intervals for postponing different types of surgical procedure. This study reports healthcare professionals' private accounts of the strategies adopted to manage the imbalance of demand and resource, using colorectal cancer surgery as a case study. Methods: Twenty-seven semistructured interviews were conducted with healthcare professionals between June and November 2020. A key informant sampling approach was used, followed by snowballing to achieve maximum regional variation across the UK. Data were analysed thematically using the constant comparison approach. Results: In the context of considerable resource constraint, surgical teams overcame challenges to continue elective cancer provision. They achieved this by pursuing a combination of strategies: relocating surgical services; prioritizing patients within and across surgical specialties; adapting patient treatment plans; and introducing changes to surgical team working practices. Despite national guidance, prioritization decisions were framed as complex, and the most challenging of the strategies to implement, both practically and emotionally. Conclusion: There is a need to better support surgeons tasked with prioritizing patients when capacity exceeds demand. Abstract : Using colorectal cancer surgery as a case study, this qualitative study represents the first in-depth investigation of how surgical teams managed to uphold surgical services in the first wave of the COVID-19 pandemic, despite contending with immense resource constraint. The findings revealed a combination of strategies pursued, including: relocating surgical services; prioritizing patients within and across surgical specialties; adapting patient treatment plans; and introducing changes to surgical team working practices. It was concluded that surgeons need to be better supported to manage the task of prioritizing patients, and raises wider questions about who should be involved in this key activity.